Pharmacovigilance of antiepileptic drug toxicity in children - Egunsola, Oluwaseun (2017)
Several of the available antiepileptic drugs (AEDs) were approved in the last 25 years. These new generation AEDs have not been shown to be more effective than the old ones and their safety profile have not been explored sufficiently in pharmacovigilance studies. As reported in chapter 2, prospective cohort studies are the most common pharmacovigilance study methods, with adverse drug reactions (ADRs) often elicited with questionnaires or checklists. A systematic review to identify all published AED side effects rating scales, reported in chapter 3, identified nine AED ADR rating scales. Two of these, The Hague Side Effect Scale (HASES) and the Paediatric Side Effect Questionnaire (PESQ), are paediatric specific. A systematic review of AED utilisation rate reported in chapter 4, shows an increasing utilisation of levetiracetam and lamotrigine reported as the most frequently utilised new generation AED in paediatrics. Systematic reviews of the safety of both drugs in children, reported in chapters 5 and 6, identified rash (7.3%) and behavioural problems (10.9%) as the most common ADRs associated with lamotrigine and levetiracetam respectively. They were also the most common reasons for the discontinuation of treatment. In chapter 7, Stevens-Johnson Syndrome (SJS) and Toxic Epidermal Necrolysis (TEN) risks are reported to be significantly higher when lamotrigine was co-prescribed with sodium valproate (43%) than when either carbamazepine (8%) or phenobarbital (8%) were co-prescribed with sodium valproate. SJS/TEN also occurred more frequently with sodium valproate and lamotrigine co-medication than other non-cutaneous ADRs (19%). Being the more recent paediatric AED ADR rating scale, the PESQ was selected for the elicitation of ADRs in a prospective cohort study of AED safety in children reported in chapter 8. Half of the 124 participants in the study received levetiracetam, either as monotherapy or polytherapy. There were significantly fewer ADRs with levetiracetam than either carbamazepine or sodium valproate monotherapy. The risks of drowsiness, fatigue and weight gain were significantly higher with levetiracetam polytherapy than monotherapy (p<0.05). Attention difficulties, aggression and decreased concentration were significantly lower with valproate polytherapy (p<0.05). The common ADRs associated with AEDs are discussed in chapter 9. In conclusion, lamotrigine and levetiracetam are increasingly being used for the treatment of epilepsy in children. Lamotrigine may cause severe rash, especially when co-administered with valproate; while levetiracetam is a common cause of behavioural problems. In order to compare the safety profile of AEDs adequately, large multicentre paediatric safety studies are required.